A concepção de escrita no livro didático Novo Avenida Brasil 1: um novo olhar sobre o ensino de português como língua estrangeira - Praxedes, José Gualberto Targino (2010)
This study raises from a question about the use of two theoretical frameworks in the development of a textbook called Novo Avenida Brazil 1: a basic course in Portuguese for foreigners, re-edited in Brazil by the Editora Universitária e Pedagógica in 2008. The first framework to be used was The Common European Framework of Reference for Languages, edited and used in the European Community, and the second one was The Certificate of Proficiency in Brazilian Portuguese for Foreigners - CELPE- Bras, the only Brazilian official certification, developed and granted by the MEC (Ministry of Education). It is the concern of the use of a foreign theoretical framework in the manufacture of a Brazilian product, which makes us look into both frameworks, and recognize that the two work with the modern conception of language in use, in which the notion of task as a tool to interact in the world with a social purpose permeates both one another, what leads us to scrutinize the activities involving the production of written texts, both in the textbook of the Novo Avenida Brasil 1, and in its workbook, both constituting a single volume of the book under examination. Adopting as concepts, dear to our vision of writing production with a social aim, the interaction and the principles of textuality, we analyzed step by step each lesson of the book in order to really understand whether these activities of writing production were contemplated, and whenever affirmative, if these activities, in fact, substantiated the theoretical basis in which the authors of the book in question claimed to support. As a result of the investigation, in the light of the conception of language underlying both theoretical frameworks, we have found the lack of writing production activities that lead the learner of Portuguese as a Foreign Language - PLE on a path that goes from planning to a final execution of the act of writing, and when we find them, they seem to neglect, so to speak, the construction of an apprentice in the new vision of literacy, in the theoretical basis of textual genres, by making use of activities of structural bases, with no social purpose, denying thus the language conceptions used by the theoretical frameworks in which they insist on saying they are settled.